2021
DOI: 10.1039/d0ra08305d
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-covered liposomes as a promising drug transporter: nanoscale investigations

Abstract: In this paper, we studied the graft chitosan conformation and its influence on the liposome membrane structure and dynamics as a function of the grafting molar-fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Meanwhile, graft density affected the diffusion and arrangement of liposomes, the polymer grafting densities increases and the diffusion coefficients decrease. Studies found that the polymers have a normal diffusion after a short regime of sub‐diffusion, and then move freely and increase the dynamic flexibility of the liposomes (Lemaalem et al, 2020; Mohammed et al, 2021).…”
Section: Characteristics Of Polysaccharide‐coated Liposomal Drug Deli...mentioning
confidence: 99%
“…Meanwhile, graft density affected the diffusion and arrangement of liposomes, the polymer grafting densities increases and the diffusion coefficients decrease. Studies found that the polymers have a normal diffusion after a short regime of sub‐diffusion, and then move freely and increase the dynamic flexibility of the liposomes (Lemaalem et al, 2020; Mohammed et al, 2021).…”
Section: Characteristics Of Polysaccharide‐coated Liposomal Drug Deli...mentioning
confidence: 99%
“…The energyminimised systems further undergo a constant enthalpy (NPH) simulation for 2000 fs using a Langevin thermostat at the desired temperature. This step is used to expedite the process of equilibration [50,56]. Following that, the system is further equilibrated under NPT conditions where Nosé-Hoover thermostat and corresponding barostat are applied to maintain temperature and pressure, respectively.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…CS and related derivatives may have significant impact on the secondary structure of keratin, increase the water content in the SC, reduce the potential of the human immortalized keratinocyte cell membrane and increase its fluidity. Such liposomal complexes with CS are called chitosomes [218]. CS can interact with the negatively charged liposome by an electrostatic mechanism due to the CS positive charge.…”
Section: Chitosomesmentioning
confidence: 99%